The role of video background cues in the virtual court: a psychological perspective - Muir, Bethany R. (Psychology, crime & law, 2025)
Remote appearances for courtroom proceedings have become common practice in recent years. When a court participant appears remotely, they introduce new and often tangential cues as part of their video background. We have seen varying (and at times, controversial) background cues across virtual court members, with scholars and legal professionals noting the potential effects these cues may have on decisions and impressions (e.g. Bandes & Feigenson, 2020). Advice is often provided for how people should appear to virtual court, but this is often made with no direct link to empirical evidence. In this piece, we review psychological literature exploring how and why background cues may influence impressions and decision-making. In particular, we examine the role of cognitive factors such as schema activation and consequences for memory and truth assessment. We further consider social factors such as the connection between physical spaces and personality in shaping impression formation and decision-making. Finally, we highlight future research opportunities to target unanswered questions and ongoing innovations in virtual courts, in addition to considering policies and procedures that can be implemented to avoid background cue effects.